Considering Leaving, But Deciding to Stay: A Longitudinal Analysis of Intent to Leave in Public Health - Bogaert, Kyle (J Public Health Manag Pract, 2019)
CONTEXT: Public health has been hit by the first wave of the “silver tsunami”—baby boomers retiring en masse. However, thousands of staff members say they are considering voluntarily leaving for other reasons as well. OBJECTIVE: To identify characteristics of staff who said they were planning on leaving in 2014 but stayed at their organizations through 2017. DESIGN: Data from the 2014 and 2017 Public Health Workforce Interests and Needs Survey (PH WINS) were linked by respondent, and characteristics associated with intent to leave were analyzed. Longitudinal logistic models were fit to examine correlates of intent to leave, with job and pay satisfaction, demographic variables, and workplace engagement perceptions as independent variables. SETTING AND PARTICIPANTS: Respondents from state health agency–central offices and local health departments that participated in the PH WINS in 2014 and 2017. MAIN OUTCOME MEASURES: Intent to leave (excluding retirement), demographic measures, and changes in the perceptions of workplace engagement. RESULTS: Among all staff members responding in 2014 and 2017, 15% said they were considering leaving in 2014, excluding retirement, compared with 26% in 2017 (P < .001). Overall, 21% of those who were not considering leaving in 2014 indicated they were doing so in 2017. Comparatively, 57% of those considering leaving in 2014 said they were still considering it in 2017. The regressions showed those who were somewhat or very satisfied were significantly more likely to indicate they were not (or were no longer) considering leaving. CONCLUSIONS: Among staff members who have been considering leaving but have not yet left their organization, improvements to workplace engagement perceptions and job satisfaction were highly associated with not considering leaving their job.